2011
DOI: 10.4081/hr.2011.e1
|View full text |Cite
|
Sign up to set email alerts
|

Osteopetrosis: A Rare Cause of Anemia

Abstract: Normocytic anaemia is caused either by hypoproliferation of haemopoietic tissue or increased destruction of red cells. Osteopetrosis is a rare cause of anaemia. Infantile osteopetrosis (also called malignant osteopetrosis) is diagnosed early in life. But it is the adult osteopetrosis (also called benign osteopetrosis) which is diagnosed in late adolescence or adulthood that present as anaemia which is difficult to diagnose and treat. Approximately one half of patients are asymptomatic, and the diagnosis is mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
0
14
0
2
Order By: Relevance
“…Indeed, several reports suggested that the aberrant bone microenvironment provokes defects in immune cell differentiation and function (Begg et al 1993). Osteopetrotic patients develop anemia and serious infection as a result of abnormal hematopoiesis (Reeves et al 1979;Gerritsen et al 1994;Sreehari et al 2011). The frequency and absolute number of Lin neg Sca-1 + c-kit + (LSK) cells are decreased in oc/oc mice, which have defective bone resorption because of a mutation in the Tcirg1 gene (Li et al 1999).…”
Section: The Bone Marrow Microenvironmentmentioning
confidence: 99%
“…Indeed, several reports suggested that the aberrant bone microenvironment provokes defects in immune cell differentiation and function (Begg et al 1993). Osteopetrotic patients develop anemia and serious infection as a result of abnormal hematopoiesis (Reeves et al 1979;Gerritsen et al 1994;Sreehari et al 2011). The frequency and absolute number of Lin neg Sca-1 + c-kit + (LSK) cells are decreased in oc/oc mice, which have defective bone resorption because of a mutation in the Tcirg1 gene (Li et al 1999).…”
Section: The Bone Marrow Microenvironmentmentioning
confidence: 99%
“…A decrease in the number of red blood cells may result in an anemia disorder. Previous literature showed a positive correlation between osteopetrosis and anemia disorder (Fischer et al, 1991;Gamsu et al, 1961;Lees and Sautter, 1979;Saluja et al, 2009;Sreehari et al, 2011). Our quantitative study of abnormal aging mice suggests that the anemia disorder may be directly linked to the internal expansion of cortical bones at diaphysis.…”
Section: Discussionmentioning
confidence: 44%
“…La osteopetrosis es una enfermedad de etiología desconocida, 7 caracterizada por una alteración funcional en los osteoclastos, incapacitándolos para la reabsorción ósea normal. 8,9 El diagnóstico es fundamentalmente clínico y radiológico; las manifestaciones clínicas que presentan los pacientes con osteopetrosis son muy variables y van en relación al grado de disfunción osteoclástica.…”
Section: Discussionunclassified